The prevalence and clinical features of epileptic seizures in a memory clinic population. (October 2019) - Baker, John; Libretto, Tina; Henley, William; Zeman, Adam
Highlights: The Prevalence of epileptic seizures in dementia is between 12.5 and 25.7%. At initial assessment cognitive scores did not differ in patients with epilepsy from those without. Patients with epilepsy were more disabled as measured by informant completed questionnaires (CDR, CBI-R). Abstract: Purpose: To determine the prevalence and clinical features of epileptic seizures occurring in a memory clinic population. Method: We recruited patients receiving a diagnosis of dementia or mild cognitive impairment (MCI) at a regional memory clinic. We interviewed patients and informants using a proforma designed to elicit symptoms suggestive of epilepsy. Informants also completed the Clinical Dementia Rating Scale (CDR) and the Cambridge Behavioural Inventory- Revised (CBI-R). Patients underwent cognitive testing using the Addenbrooke's Cognitive Examination – III (ACE-III). We also recruited an age- and gender- matched control group with no history of cognitive impairment. Diagnoses of dementia/MCI were checked against current diagnostic criteria. Results: We recruited 144 patients (mean age 77.98, mean ACE-III 74.16, 124 with dementia, 20 with MCI). We diagnosed epilepsy in 25.7%: probable in 12.5% (17 with dementia, 1 with MCI), possible 13.2% (18 with dementia, 1 with MCI). Seizure features included altered responsiveness, speech/behavioural arrest, oral/pharyngeal automatism, olfactory/gustatory aura, focal motor seizure, other sensory phenomena (including hallucination), and amnesia on waking. Epilepsy prevalence was significantly increased in the dementia and MCI group vs controls (p = 0.004). Cognitive performance in the patient groups did not distinguish those in whom epilepsy was suspected from those in whom it was not. Patients in whom epilepsy was suspected were more impaired on informant completed measures of daily function. Conclusions: The prevalence of epilepsy is increased in dementia. The seizures are often subtle and easily missed. The presence of epilepsy predicts more severe impairment in the activities of daily living.